Aging Effects on Absolute and Relative Estrogen Receptor Variant Gene Expression Levels in Male Versus Female Rat Ventromedial Hypothalamic Nucleus Growth Hormone-Releasing Hormone Neurons - Rami Shrestha; Subash Sapkota; Karen P. Briski (Journal of Integrative Neuroscience)
Background: Aging alters estrogen receptor (ER) expression in distinctive hypothalamic loci, but information regarding potential adjustments in estradiol receptivity at the individual neuron population level remains incomplete. Estradiol controls glucostasis by action on ventromedial hypothalamic nucleus (VMN) targets. VMN growth hormone-releasing hormone (Ghrh) neurons exhibit sex-dimorphic ER variant and counterregulatory transmitter gene profiles in young adult rats. Methods: Combinatory single-cell laser-catapult-microdissection/multiplex qPCR analyses was used to investigate whether aging changes nuclear versus cytoplasmic ER gene expression according to sex. Results: Ghrh neuron ER-alpha and G-protein-coupled estrogen receptor-1 (GPER) transcription was decreased in old versus young rats of each sex. Old animals lacked ER-alpha transcriptional reactivity to hypoglycemia, indicative of age-associated loss of response. Hypoglycemia had divergent effects on ER-beta transcription, with no effect found in old males versus an inhibitory effect in old female rats. Hypoglycemic inhibition of Ghrh neuron GPER gene expression in old male and female rats was similar to that which occurred in corresponding young animals. Ghrh gene silencing identified age-related loss of neuropeptide modulatory regulation of ER gene transcription. Ghrh signaling inhibited eu- and hypoglycemic Ghrh neuron aromatase/CYP19A1 mRNA profiles in old male and female rats; in each sex, this gene transcript was refractory to hypoglycemia regardless of age. Conclusions: VMN Ghrh neuron neuroestradiol production may be up-regulated with age, but cellular sensitivity to this local steroid signal may differ between young and old rats due to differences in ER variant expression. Further research is warranted to examine how potential age-associated modifications in absolute and proportionate signaling by distinctive ER may affect Ghrh neuron glucose-regulatory neurotransmission in male versus female rats.